RESPONS MASYARAKAT TERHADAP TWEET USTADZ FELIX SIAUW: âLAYAKKAH WANITA BEKERJA MENDAPAT SEBUTAN SEBAGAI IBU?â - Handayani, Maya Rini (Sawwa: Jurnal Studi Gender, 2016)
Islam is a perfect religion. A religion which is always honor a woman. In Islam there is no prohibition of a woman to work for a living, as long as follow the terms and conditions according to Islam. Ustad Felix Siauw once twote some statement which was associated with working mothers in his Twitter on 28 May 2013. The amount of the tweet is 25, but the spotlight later evolved into the conversation is tweet #22. It became viral since a working mother wrote an open letter to comment the tweet #22 . This article discusses the phenomenon of public response from various backgrounds and religions to the #22 tweet, and also comments and reasons of ustad Felix Siauw write that tweet.